The Influence Of Academic Supervision On Teacher Performance Based On The Philosophy Of Essentialism - Anastasia Moertodjo; Siti Masitoh; Mochamad Nursalim (Institute of Computer Science (IOCS), 2022)
Very quality education and learning depending on how well the quality of the teacher's performance is in carrying out his academic duties at school. Teacher performance influenced by many factors including supervision principal, professional competence, job satisfaction and teacher motivation. All four factors should workin an integrated and sustainable way to have an impact good to teacher performance. The method used is with a literature approach .surveillance approach in education conducted by the principal's office as a supervisor has a primary role as supporters of the educational process in schools. Understanding Challenge Academic Supervision in an Epitemological Perspective which is part of philosophy and origin Academic Oversight Inquiry